Pengaruh Rasio Lancar, Rasio Cepat, Rasio Kas dan Rasio Utang dengan Ekuitas terhadap Profitabilitas: (Studi Empiris pada Perusahaan Sub Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019 – 2023) - Saddam Cato; Roza Fitriawati (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to determine the effect of Current Ratio, Quick Ratio, Cash Ratio and Debt to Equity Ratio on Profitability in Property and Real Estate sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2023 as many as 93 companies. The data used in this study were obtained from financial report data and annual reports. The population in this study were property and real estate sector companies listed on the Indonesia Stock Exchange. The sampling technique used was the Purposive Sampling method and obtained 44 companies. The data analysis technique used in this study was a multiple linear regression analysis test using the Statistical Package For the Social Sciences (SPSS) version 22 program. The results of this study indicate that the current ratio and debt to equity ratio do not have a significant effect on profitability, the Quick ratio has a negative and insignificant effect on Profitability while the cash ratio has a significant effect on Profitability.